Trafficking and Technology: Exploring the Role of Digital Communication Technologies in the Belgian Human Trafficking Business - Raets, Sigrid (European journal on criminal policy and research, 2021)
Over the past few years, the agenda-topping issue of human trafficking is increasingly bracketed with the use of digital technologies. Though the trafficking-technology nexus is a growing area of public and policy concern, as far as empirical research is concerned, the subject is still a relatively open field. As a result, quite a few unknowns regarding the interaction between technological developments and trafficking in persons remain unresolved. In this context, the present research paper principally aims to build on the existent body of literature in order to broaden our comprehension of the matter at hand. Based on a systematic literature review and interviews with convicted offenders as well as anti-trafficking practitioners in Belgium, this paper presents an overview of the various ways in which technology can be leveraged both in the perpetration and the counteraction of human trafficking activities. In addition, the question of how technology relates to the traditional workings of trafficking is considered from a cyber-criminological point of view. That is, a connection is drawn between the use of technological tools by human traffickers and our current understanding of the business of trafficking in persons.